Improving Silver Birch (Betula pendula) Growth and Mn Accumulation in Residual Red Gypsum Using Organic Amendments - Zapata-Carbonell, José; Ciadamidaro, Lisa; Parelle, Julien; Chalot, Michel; Tatin-Froux, Fabienne (Frontiers in Environmental Science, 2020)
The increasing production of waste that is landfilled might contribute to sources of potentially toxic elements; this is the case of residual red gypsum tailings, a by-product of titanium dioxide extraction. Revegetation of the site is essential, and phytoextraction of Mn may render the operations economically profitable. This study aimed to apply phytomanagement techniques in order to increase the plant development for revegetation and an optimal Mn phytoextraction using silver birch, the most abundant plant species on the site. To increase the availability of nutrients from the tailings, amendments that reduce the pH, such as pine bark, Miscanthus straw, white peat and ericaceous compost, were mixed with residual red gypsum and birches were allowed to grow for 3 months. The pine bark and ericaceous compost showed a maximum decrease in pH, allowing up to 1400 mg kg-1 dry matter of Mn to be phytoextracted by the silver birch. However, some nutrient competition was found in the treatment of pine bark, which affected biomass production by reducing it by half compared to control.. Further amendment additions may be needed to take advantage of the pine bark capabilities as a nutrient and Mn solubilizing treatment in residual red gypsum.